Due South: A first assessment of the potential impacts of climate change on Cape vulture occurrence. (June 2017) - Phipps, W. Louis; Diekmann, Maria; MacTavish, Lynne M.; Mendelsohn, John M.; Naidoo, Vinny; Wolter, Kerri; Yarnell, Richard W.
Abstract: Multiple anthropogenic threats have caused vulture populations to decline globally, with serious ecological and socio-economic implications. The Cape vulture ( Gyps coprotheres ) has declined throughout its range in southern Africa, recently being listed as extinct as a breeding species in Namibia. It has been suggested that climate change might have contributed to the decline of Cape vultures in northern parts of the range. To provide a first assessment of the potential impacts of climate change on the occurrence of Cape vultures, a presence-only environmental niche modelling method (Maxent) was used to predict the spatial occurrence patterns of wild vultures fitted with GPS tracking units in northern Namibia and northern South Africa, under current and future climatic conditions. The models showed high predictive power (AUC > 0.868 ± 0.006), with precipitation seasonality identified as the most important variable for predicting Cape vulture presence. Of the area estimated to be suitable for Cape vultures under current conditions, 28–55% was predicted to become unsuitable under future climate conditions, with a pole-ward shift in the mean centre of the range of 151–333 km and significant range loss from the former breeding range in north-central Namibia and the core breeding range in northern South Africa. The total area of suitable range was predicted to increase in the future due to modelled expansions into grassland and cropland areas where the species has been absent historically. The coverage of suitable areas by protected areas was predicted to decrease from 5.8–7.9% to 2.8–3.8%, suggesting that private land will become increasingly important for Cape vulture conservation. Highlights: Cape vulture occurrence assessed by presence only environmental niche models First description of environmental characteristics of Cape vulture spatial niche Models predict southwards shift of suitable conditions away from core colonies. Coverage of suitable range by protected areas predicted to decrease Climate change should be considered in global vulture conservation strategies.